SABAR DALAM PERSFEKTIF AL-QUR’AN - Andi Miswar (Al-Hikmah Journal for Religious Studies, 2017)
Patient is the ability of some one to endure from difficulty of life and to control emotion for the shake of reaching a target. People are often confronted by collision or condition that bring them into insulation, dissapointment and stress. So that patient can become control of some one personally and socially. Patience does not mean surrender bacause it some time brings someone into fatalism. Patient is a word that covers a whole set of moral values that’s most infortant. In fact, patient is a key from some one to success. Qur’an also suggest to use patient as benefactor in facing all aspect of life’s temptation.